Assessment of Wood - Saavedra-Flores, E; Garcia-Herrera, C; Vasco-Calle, D; Alvarez-Carrasco, F (Elsevier, 2024)
In recent years, wood has gained great popularity among engineers, builders, and architects, particularly in the construction sector. This is due to the physical and mechanical properties of wood along with its sustainable nature, which make it an excellent building material. However, understanding wood properties requires first the comprehension of wood microstructure to explain these outstanding features. At microscopic scales, wood is a porous and hygroscopic material whose anisotropic nature affects its mechanical and thermal properties. The orthotropic behavior of wood has a special influence on the wood’s mechanical response, which is fundamental during the manufacturing processes of wood products for construction. The thermal conductivity and thermal inertia of construction materials play a vital role in the response of the thermal envelope, which influences the thermal performance and the thermal comfort of the residents of the building. The present contribution adds to what has been published so far in the context of the mechanical and thermal properties of wood at macro and microscales and its environmental and socioeconomic impacts on the mass timber construction sector. © 2024 Elsevier Ltd. All rights reserved.